1989
DOI: 10.1152/ajpregu.1989.257.3.r618
|View full text |Cite
|
Sign up to set email alerts
|

Physiological role of HMG-CoA reductase in regulating egg production by Schistosoma mansoni

Abstract: Pathological lesions observed in humans infected with Schistosoma mansoni are due to the eggs produced by the female parasite. Mevinolin, a potent inhibitor of the enzyme hydroxymethylglutaryl-CoA (HMG-CoA) reductase, blocks egg production by this parasite. In this report, we demonstrate that cholesterol precursors, mevalonate and farnesol, stimulate egg production by the female parasite and that these precursors can reverse the mevinolin-induced inhibition of egg production. Because the parasite cannot synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…The FPPS enzyme assays were performed essentially as described previously (31), using 14 Clabeled IPP with DMAPP, GPP, and FPP. One hundred microliters of assay buffer containing 10 mM HEPES, pH 7.4, 5 mM MgCl 2 , 2 mM dithiothreitol, 47 M [4-…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations
“…The FPPS enzyme assays were performed essentially as described previously (31), using 14 Clabeled IPP with DMAPP, GPP, and FPP. One hundred microliters of assay buffer containing 10 mM HEPES, pH 7.4, 5 mM MgCl 2 , 2 mM dithiothreitol, 47 M [4-…”
Section: Figmentioning
confidence: 99%
“…The GGPPS assays were performed as described previously (39,40), using 14 C-labeled IPP with DMAPP, GPP, and FPP. The 20-l assay setup consisted of 25 mM HEPES, 2 mM MgCl 2 , 0.5% n-octyl-␤-glycopyranoside, 10 M [4-…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…HMGCoA reductase inhibitors have been shown to have activity against schistosoma parasites (www.wipo.int/research/en/collaboration), and investigation of their potential continues. 57,58 Kinase inhibitors, many of which have been developed in the pharmaceutical industry as oncology treatments, are promising targets in parasitic protozoa, which have related kinases, 59 for example kinetoplastid protozoa. 60 An alternative approach is serendipitous screening of panels of mature compounds in whole-pathogen assays; for example, Gloeckner et al (2010) 61 used the Johns Hopkins Clinical Collection to identify Closantel, a veterinary antihelmintic, as active on Onchocerca volvulus, the nematode that causes river blindness; whereas Abdulla et al (2009) 62 have identified compounds that have hit-and lead-like properties for the treatment of schistosomiasis.…”
Section: Neglected Tropical Diseasesmentioning
confidence: 99%